Takfir dalam Pandangan Ibn Taimiyah Kajian atas Kitab Majmu' Fatawa - Hartono, Rudi (2016)
Ibn Taimyah was either a scholar or mujahid of principle until the end of life. He was a scholar with overflow work, master a variety of disciplines, experts in law of istinbat, his written speeds as his fast as spoken language. He is a mujahid who feels the bitter life in the battlefield of jihad against the Tartars. There are many hostiles until he had to feel the prison. However, he works tirelessly for the spirit of reconciliation and tajdid movement in his time. This study is a library (library research) using theological approach, which is intended to examine how the concept of takfir according to Ibn Taimiyah ideas which is contained in the book of Majmu' Fatawa and its relevance at the present. Source of data used in this study is the book of Ibn Taimiyah Majmu' Fatawa as primary data, particularly related with terms takfir. As a secondary data, it also studied with others Ibn Taimiyah works and the works of others related to the theme of takfir. Once collected by the method of documentation, these data will be processed using the method of content analysis. Based on the research results, in the book of Majmu>' Fatawa Ibn Taimiyah consider as one whom very careful in determining the verdict infidels, mainly related to takfir ta'yin. This prudent attitude on the issue of takfir Ibn Taimiyah does not mean bore underestimation attitude of takfir law. If certain parties are clearly and evidently has done the practices of paganism qualify takfir and no barriers, he did not hesitate to assign as a verdict infidels. Ibn Taimiyah is very firm to bear among exaggerated in applying the concept of takfir, or people who underestimate this concept of takfir. Thus, he proved with a number of factors that make certain parties exaggerate or underestimate in applying the concept of takfir. It also proves that Ibn Taymiyyah has a mid stance (at-tawasut) in bearing and applying the concept of takfir. The concept of takfi>r offered by Ibn Taimiyah in the book of Majmu' Fatawa has very strong relevance at present, especially with Islamiyah propaganda in general, and the qualities of a preacher particularly related to the Indonesian context, the concept of takfir also have relevance to MUI decision on ten cult criteria. The points in the decision has interrelated meanings with the explanation of about concept of takfir by Ibn Taimiyah in the book of Majmu' Fatawa.